French Mediterraneans : Transnational and Imperial Histories - Shepard, Todd, 1969-; Lorcin, Patricia M. E. (Book collections on Project MUSE., 2016)
"Collection of essays that explore the French presence in the 19th and 20th-century making of the Mediterranean"--Provided by publisher.